The Hardy Picture of a Wife (Case Study on the Wife what are the Background of the Family) - Ahmad Shofyan Chabib; Wiwin Hendriani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Hardiness is a series of personalities in every human being acquired through genetic inheritance and accumulation of life experience. A person will have hardiness if he has good self-commitment, self-control, and self-challenge. In addition to genetic inheritance, hardiness formation can also occur through situations and conditions encountered, which creates a convenience toward the situation being experienced, experienced and done. One of the vital functions of a person, especially a wife who acts as the backbone of the family, is creating self-defence so that she feels stronger and more convenient in dealing with any problem in life.  This research employs a qualitative method using a case study approach where the researcher observes all family activities. In this research, the researcher is taking a role as the main instrument of data collection and identification by exposing and describing the data toward the research object. For validity, field data revision, and source triangulation. This research suggests seven problems associated with a wife who acts as the backbone of a family. These include a. self-time management, b. self-hesitant and doubt, c. self-enforcement to work, d. lack of social support from their family and surrounding, e. lack of tolerance or empathy, f. ignorance and Negligence from their family and surrounding, g. they are becoming the object of talk (bullying). Formation of hardiness on a wife acting as the backbone of a family occurred through four phases: a. existence of self-obsession and commitment, b. existence of spirit and belief to archive the obsession, d. change of traits and attitudes. Furthermore, eight factors contribute to the formation of a hardy personality. These include a. having hope within oneself, b. act independently, c. self-confidence, d. self-disclosure, e. social support, f. being modest, g. religiosity, h. thankful